Biomass carbon aerogels based shape-stable phase change composites with high light-to-thermal efficiency for energy storage. (June 2020) - Wang, Chengjun; Liang, Weidong; Yang, Yueyue; Liu, Fang; Sun, Hanxue; Zhu, Zhaoqi; Li, An
Abstract: The development of high-performance shape-stable phase change materials composites (ss-PCMCs) with enhanced thermal conductivity and high phase change enthalpy is of great importance for thermal energy storage. Herein, we report the creation of novel ss-PCMCs by incorporation of organic PCMs (1-hexadecanamine (HDA) and palmitic acid (PA)) into the biomass carbon aerogels (BCAs refer to sunflower receptacle spongy carbon aerogel (r-CA) and sunflower stem carbon aerogel (s-CA)) through a simple vacuum infusion. Due to their abundant porosity, light weight and high specific surface area, organic PCMs can be spontaneously loaded into BCAs with an ultrahigh loading rate of up to 1988 wt%. The obtained of PCM/BCAs composites show high phase change enthalpy of ranging from 207.9 kJ kg −1 to 271 kJ kg −1, in addition to their excellent thermal stability and recyclability, e.g., their phase change enthalpy nearly remains unchanged even after 50 times of melting/freezing cycles. The PCM/BCAs composites also show an enhanced thermal conductivity. Furthermore, the light-to-thermal conversion efficiency was found to be promising candidates for light-to-thermal energy storage applications on basis of their 75.6% for HDA/r-CA and 67.8% for HDA/s-CA, respectively, making them abundant resource, cost-efficiency, simple and scalable fabrication process. Highlights: HDA was first exploited as a new class of phase change material. ss-PCMCs were fabricated by doping of PCM into biomass carbon aerogels of sunflower. The HDA/BCAs shows high light-thermal conversion efficiency (67.8%–75.6%). The loading rate of HDA in BCAs is up to 1988 wt % and 873%, respectively.